2020
DOI: 10.1007/s00296-020-04619-z
|View full text |Cite
|
Sign up to set email alerts
|

Up to 5-year retention of abatacept in Belgian patients with moderate-to-severe rheumatoid arthritis: a sub-analysis of the international, observational ACTION study

Abstract: Favorable efficacy and safety profiles have been demonstrated for abatacept in patients with rheumatoid arthritis (RA) in randomized controlled trials, but these data require validation during long-term follow-ups in routine clinical practice. This study explored long-term safety and retention rates in RA patients treated with intravenous abatacept in the Belgian cohort of the international AbataCepT In rOutiNe clinical practice (ACTION) study (NCT02109666). This non-interventional, observational, longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…On the other hand, in our study, ACPA positivity and the concomitant assumption of MTX were associated with a slightly higher RR at 60 months, even if not statistically signifi- ORIGINAL PAPER cant (Figure 1D, E), likely due to the limited sample size. This data is in accordance with the results of other studies (12)(13)(14)(15).…”
Section: N Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, in our study, ACPA positivity and the concomitant assumption of MTX were associated with a slightly higher RR at 60 months, even if not statistically signifi- ORIGINAL PAPER cant (Figure 1D, E), likely due to the limited sample size. This data is in accordance with the results of other studies (12)(13)(14)(15).…”
Section: N Discussionsupporting
confidence: 93%
“…In this study, we evaluated the response to ABA in patients with RA through RR, which is considered a good predictor of effectiveness and safety in real-life scenarios. This issue has been evaluated in other studies, which are summarized in Table II (12)(13)(14)(15)(16)(17).…”
Section: N Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Lahaye et al have reported that ABT was effective even in RA patients with >75 years in the French cohort (ORA registry), and the risk of severe infection should be considered in such patients [ 3 ]. A Belgian cohort study (sub-analysis of the ACTION study) also showed sustained long-term retention rates (up to 5-year retention) in RA patients treated with ABT [ 9 ]. ABT treatment has been reported to have relatively higher retention rates than other biologics [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of belatacept, a second-generation CTLA4Ig that differs from the original form by two amino acids, is associated with a high incidence of post-transplant lymphoproliferative disorder in the subsets of kidney transplantation patients [ 8 ]. As a result, patients may discontinue CTLA4Ig therapy due to severe adverse effects [ 9 , 10 ]. Furthermore, CTLA4Ig is associated with an increased incidence of skin cancers [ 11 , 12 ], raising the concern that long-term systemic suppression of T cells by this agent may compromise cancer immunosurveillance.…”
Section: Introductionmentioning
confidence: 99%